Elementary school staff knowledge about management of traumatic dental injuries - Al-Sehaibany FS; Almubarak DZ; Alajlan RA; Aldosari MA; Alqahtani ND; Almaflehi NS; AlBarakati SF (Dove Medical Press, 2018)
Fares S Al-Sehaibany,1 Danah Z Almubarak,2 Reem A Alajlan,2 Mohammad A Aldosari,1 Nasser D Alqahtani,1 Nassr S Almaflehi,3 Sahar F AlBarakati1 1Department of Pediatric Dentistry and Orthodontics, College of Dentistry, King Saud University, Riyadh, Saudi Arabia; 2Dental Intern, College of Dentistry, King Saud University, Riyadh, Saudi Arabia; 3Department of Periodontics and Community Dentistry, College of Dentistry, King Saud University, Riyadh, Saudi Arabia Aim: This study investigated the knowledge of elementary school staff regarding the management of traumatic dental injuries (TDIs) in children.Methods: The present cross-sectional study analyzed data collected between September 2016 and April 2017. The sample consisted of 2,027 elementary school staff members in Riyadh, Saudi Arabia. A stratified cluster random sampling technique was used to select the required sample. Those who agreed to participate in the study completed a 4-part self-administered questionnaire comprising questions regarding demographic data, knowledge on management of tooth fracture, and avulsion using photographs of TDI cases.Results: The majority of the school staff showed inadequate basic knowledge regarding the importance of saving the broken piece of the tooth and identifying the tooth involved in the trauma (67% and 66.3%, respectively), P<0.05. However, they had a significantly high number of correct responses regarding the immediate management of TDIs for the 2 case scenarios presented in the questionnaire (P<0.05), and the majority (41%) reported normal saline as a suitable storage medium (P<0.01).Conclusion: This study revealed a lack of knowledge in certain aspects of TDIs among elementary school staff. Keywords: school staff, knowledge, traumatic dental injuries